2011
DOI: 10.1007/s11064-011-0509-z
|View full text |Cite
|
Sign up to set email alerts
|

Acute Restraint Stress in Zebrafish: Behavioral Parameters and Purinergic Signaling

Abstract: Despite the extensive knowledge about the effects of acute restraint stress (ARS) in rodents, zebrafish research is still elementary in this field, and the consequences of stress on purinergic system are unclear. Therefore, we evaluated the effects of ARS on behavior, biochemical, and molecular parameters in zebrafish brain. Animals were submitted to a 90 min ARS protocol and tested for anxiety levels, exploratory behavior, and memory performance. Furthermore, we analyzed ectonucleotidase and adenosine deamina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 65 publications
0
32
0
Order By: Relevance
“…Meanwhile, the same stress protocol was able to induce an increase on ATP hydrolysis, without changes in the ADP or AMP hydrolysis in rat hippocampal synaptosomes [57]. Piato and colleagues [18] showed that acute restraint stress significantly increased ATP hydrolysis, decreased cytosolic ADA activity, and altered the entpd and adora gene expression. In our study, there were no significant changes on ectonucleotidase activities (NTPDase and ecto-5′-nucleotidase) after the exposure to UCS protocol in zebrafish brain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, the same stress protocol was able to induce an increase on ATP hydrolysis, without changes in the ADP or AMP hydrolysis in rat hippocampal synaptosomes [57]. Piato and colleagues [18] showed that acute restraint stress significantly increased ATP hydrolysis, decreased cytosolic ADA activity, and altered the entpd and adora gene expression. In our study, there were no significant changes on ectonucleotidase activities (NTPDase and ecto-5′-nucleotidase) after the exposure to UCS protocol in zebrafish brain.…”
Section: Discussionmentioning
confidence: 99%
“…UCS changes brain physiology and neural circuits [14] and leads to the development of depressive behaviors [15]. In mammalians, the hypothalamic-pituitary-adrenal (HPA) axis and the sympathetic nervous system (SNS) have a major role on physiological stress response in the body and constitute the main effector pathways of the stress system, mediating their adaptive functions [3,16] Zebrafish is a helpful model organism to evaluate stress and anxiety [17][18][19][20] and is useful for assessing behavioral and molecular mechanisms of brain disorders [21][22][23], developmental biology, pathophysiology of metabolic diseases, and neurodegeneration [24][25][26][27]. There is a high degree of homology between zebrafish and humans, as the presence of a homologue of the HPA axis, the hypothalamic-pituitary-interrenal axis (HPI).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies showed that acute restraint stress enhanced ROS production in the brain [42] and modified purinergic signalling in adult fish [43]. Considering that caudal fin amputation triggers ROS production which is essential for regeneration [10], we decided to test directly whether the purinergic signalling engaged by apoptotic cells during adult caudal fin regeneration is of importance for cell plasticity, i.e.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…S1). Four adenosine receptor (AdoR) subtypes (A1, A2A, A2B and A3) and two transporters (ENT1 and 2) have been identified in vertebrates [46] and the subtypes A1 [43] as well as A2A and B [47] studied in zebrafish [41]. After caudal fin amputation, the fish were incubated in agonists or an antagonist of AdoR, and the size of the regenerate was analysed at 3 dpa (Fig.…”
Section: Purinergic Pathway Downstream Of Apoptotic Cells Is Essentiamentioning
confidence: 99%